Turning and multitask gait unmask gait disturbance in mild‐to‐moderate multiple sclerosis: Underlying specific cortical thinning and connecting fibers damage. Issue 3 (21st November 2022) - Chen, Qingmeng; Hattori, Takaaki; Tomisato, Hiroshi; Ohara, Masahiro; Hirata, Kosei; Yokota, Takanori
Abstract: Multiple sclerosis (MS) causes gait and cognitive impairments that are partially normalized by compensatory mechanisms. We aimed to identify the gait tasks that unmask gait disturbance and the underlying neural correlates in MS. We included 25 patients with MS (Expanded Disability Status Scale score: median 2.0, interquartile range 1.0–2.5) and 19 healthy controls. Fast‐paced gait examinations with inertial measurement units were conducted, including straight or circular walking with or without cognitive/motor tasks, and the timed up and go test (TUG). Receiver operating characteristic curve analysis was performed to distinguish both groups by the gait parameters. The correlation between gait parameters and cortical thickness or fractional anisotropy values was examined by using three‐dimensional T1‐weighted imaging and diffusion tensor imaging, respectively (corrected p < .05). Total TUG duration (>6.0 s, sensitivity 88.0%, specificity 84.2%) and stride velocity during cognitive dual‐task circular walking (<1.12 m/s, 84.0%, 84.2%) had the highest discriminative power of the two groups. Deterioration of these gait parameters was correlated with thinner cortical thickness in regional areas, including the left precuneus and left temporoparietal junction, overlapped with parts of the default mode network, ventral attention network, and frontoparietal network. Total TUG duration was negatively correlated with fractional anisotropy values in the deep cerebral white matter areas. Turning and multitask gait may be optimal to unveil partially compensated gait disturbance in patients with mild‐to‐moderate MS through dynamic balance control and multitask processing, based on the structural damage in functional networks. Abstract : Total duration during the timed up and go test and stride velocity during cognitive‐DT circular walking are sensitive measures to evaluate gait disturbances in mild‐to‐moderate multiple sclerosis (MS). Patients with MS have impaired dynamic balance control and multitask processing correlating with regional cortical thinning and microstructural damage in major white matter tracts, involving the functions of the default mode network, ventral attention network, and frontoparietal network.